Conceptual design and assessment of a novel energy management system for LNG fueled ships with air separation. (1st December 2021) - Wang, Zhe; Han, Fenghui; Jiang, Yuemao; Yu, Shui; Ji, Yulong; Cai, Wenjian
Highlights: The feasibility of shipborne cryogenic ASU for LNG ships is demonstrated. LNGEMSs with different pressure matching processes are proposed and contrasted. The effect of pressure matching strategy on ASU and LNGEMSs are considered. Efficiency, heat load, exergy economic, and ship energy indicators are evaluated. Abstract: Medium and large ships always need to carry many different types of gas cylinders. Limited by the hull, their gas storage is small, restricting the ship's ocean voyage time. It is the most effective solution to use the air separation device and cabin air to prepare various purified gases on site. However, the traditional cryogenic air separation system has large energy consumption and low efficiency, which is not suitable for shipboard use. Therefore, this paper innovatively proposes the air separation systems for the cold energy utilization of onboard LNG-powered ships. According to the characteristics of ship engine power and pressure ratio change of LNG fuel supply system, LNG energy management systems (LNGEMSs) with high and low pressure matching cold energy utilization air separation unit processes are proposed and compared. The exergetic analysis model of the design was established using pinch point analysis, energy balance methods, and energy efficiency indexes. The applicability conclusion was determined through actual onshore process verification, comparison, and exergy analysis. The cryogenic air separation system on LNG fueled ships can adopt a different pressures heat exchange network solution to make full use of LNG cold energy to improve energy efficiency. The LNG cold exergy efficiency of the LNGEMSs can reach 83.2%, and the unit liquid product energy consumption is only 0.225 kWh·Nm −1 . Due to the additional means of energy conversion and utilization, the ship design and operating indexes with the new system meet or exceed the current regulations and the current technical level. Additional oxygen obtained by air separation can further improve the combustion efficiency of marine gas turbines, which brings good prospects for marine air separation technology.